Climate policy, technology choice, and multiple equilibria in a developing economy - Daiju Narita (Kiel Institute for the World Economy (IfW), 2010)
Control of carbon dioxide emissions in developing countries is becoming a key issue in the international climate policy. A critical element for achieving substantial emission reduction in those countries is the installment of new energy technologies. Drawing on the framework of poverty-trap models in development economics, we discuss how climate policy affects the transition of energy technologies in a developing economy. We show that while a moderate carbon policy could promote transition to low-emission energy technology, too stringent policy in a relatively poor economy may rather hinder the process by reducing the economy's financing capacity as to building new energy infrastructure - there, the barrier is not the long-run costs of the new technology but the availability of financial resources for initial investment, which could be constrained not only by the domestic saving but also by the imperfection of credit market. The possibility of such a trapping may provide a justification for financial support towards the deployment of alternative energy technologies in low-income economies.
Keywords: O16; O33; Q54; Q56; 330; Climate policy; technology choice; credit market imperfection; climate funds